2015
DOI: 10.1115/1.4030177
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Laser Welding of Direct-Quenched Ultrahigh Strength Steels: Evaluation of Hardness, Tensile Strength, and Toughness Properties at Subzero Temperatures

Abstract: The recently developed direct-quenched ultrahigh strength steels (UHSS) possess an appropriate combination of high tensile strength and toughness properties at subzero temperatures down to −80 °C, while simultaneously having low carbon contents, which is beneficial for weldability. In this study, butt joints of Optim 960 QC direct-quenched UHSS with a thickness of 8 mm were welded with a 10 kW fiber laser to evaluate the characteristics of the joints within the range of low to high heat inputs possible for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Nano-sized carbides in ferrite matrix formed by micro-alloying elements help avoiding excessive softening in the HAZ [8]. Welding methods, in which the heat input is restricted, may result in improved weld properties as reported by Farrokhi et al [9]. Farrokhi et al reported about fiber laser welding (10 kW) of direct quenched ultra-high strength steel (yield strength of 960 MPa).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nano-sized carbides in ferrite matrix formed by micro-alloying elements help avoiding excessive softening in the HAZ [8]. Welding methods, in which the heat input is restricted, may result in improved weld properties as reported by Farrokhi et al [9]. Farrokhi et al reported about fiber laser welding (10 kW) of direct quenched ultra-high strength steel (yield strength of 960 MPa).…”
Section: Introductionmentioning
confidence: 96%
“…Farrokhi et al reported about fiber laser welding (10 kW) of direct quenched ultra-high strength steel (yield strength of 960 MPa). High quality welds were obtained with good impact toughness values up to −40 • C [9]. The weld bead geometry and mechanical properties of the weld can also be improved by small modifications in the welding process, like utilizing activating fluxes during arc welding with solid wire.…”
Section: Introductionmentioning
confidence: 99%
“…Many are looking for technologies that will solve the environmental problems related to manufacturing, see, e.g., Refs. [1] and [2]. In 2001, a comprehensive study on environmentally benign manufacturing, however, found that there was no evidence that the environmental problems from our production systems are solvable by a "silver bullet" technology [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A special feature of welding of low-alloyed high-strength steels is their sensitivity to overheating with deterioration of the metal properties of the heat-affected zone (HAZ), the tendency to cold cracks in the overheating area or in the weld where metal hardening occurs during welding, and the occurrence of loss-of-strength zones in the HAZ outside the quench areas [1, 3,5,[7][8][9][10][11]. Cracking is avoided by slowing down the cooling during welding, performing various kinds of heating, which complicates the technological process and worsens the working conditions of the staff, post-weld heat treatment or using high-alloyed electrode materials [1-3, 12-14].…”
Section: Introductionmentioning
confidence: 99%